PRECARIOUSNESS AND FEMININE SUBVERSION IN THE AMAZON OF DALCÍDIO JURANDIR - das Chagas Lacerda, Oclécio (Seven Editora, 2025)
In this article, I intend to conduct a philosophical analysis of two metaphors by Dalcídio Jurandir. The first is found in the novel, "It Rains in the Fields of Cachoeira," which I call "The Metaphor of the Crucifix and the Skyscrapers." It describes the room where the prostitute Felícia lives in precarious conditions. The second metaphor, which I call "The Metaphor of the Heretical Body," is described in the novel "Marajó," when Jurandir narrates, through the character Ramiro, Orminda’s sexual relationship with the sacristan in the church tower. Based on the analysis of these two metaphors, I aim to conduct a philosophical reflection on the issue of gender and patriarchy, using as a theoretical foundation Butler’s conception of the performative body, Fraisse’s conception of gender as outside the primary gaze, Bourdieu’s conception of the symbolic mechanisms of domination, and Kristeva’s semiotics of body politics. DOI: https://doi.org/10.56238/sevened2025.029-051